The Influence of Dynamic Capabilities in Bridging Search Engine Optimization, Social Media, and Personalization with Economic Performance - Osrita Hapsara; Ignatius Septo Pramesworo; M. Ramadhan; Sigit Sugiardi; Rudianto (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study investigates the role of dynamic capabilities as a mediating mechanism that bridges SEO, social media marketing, and Personalization with economic performance. Grounded in the Dynamic Capability Theory and Resource-Based View (RBV), this research aims to understand how digital marketing practices contribute to firm performance in a dynamic business environment. Using Partial Least Squares-Structural Equation Modeling (PLS-SEM), the findings reveal that SEO and social media marketing have a positive and significant impact on dynamic capabilities. At the same time, Personalization does not show a significant effect. Furthermore, dynamic capabilities have a positive and significant influence on economic performance, confirming their strategic importance. Mediation analysis indicates that dynamic capabilities significantly mediate the relationship between SEO and economic performance, as well as between social media marketing and economic performance, but not between Personalization and economic performance. These results highlight that a firm's ability to adapt, integrate, and reconfigure its digital resources is essential to achieving superior economic outcomes. The study contributes to the ongoing discourse on digital transformation and strategic marketing by emphasizing dynamic capabilities as the key mechanism linking digital marketing strategies to economic success.